Physiological Properties and Salmonella Growth Inhibition of Probiotic Bacillus Strains Isolated from Environmental and Poultry Sources. (26th May 2013) - Menconi, Anita; Morgan, Marion J.; Pumford, Neil R.; Hargis, Billy M.; Tellez, Guillermo
Abstract : The objective of the present study was to describe the physiological properties of seven potential probiotic strains of Bacillus spp. Isolates were characterized morphologically, biochemically, and by 16S rRNA sequence analyses for identification. Tolerance to acidic pH, high osmotic concentrations of NaCl, and bile salts were tested. Isolates were also evaluated for their ability to metabolize different carbohydrates sources. The antimicrobial sensitivity profiles were determined. Inhibition of gastrointestinal Salmonella colonization in an avian model was also evaluated. Five strains of Bacillus were tolerant to acidic conditions (pH 2.0) and all strains were tolerant to a high osmotic pressure (NaCl at 6.5%). Moreover, all strains were able to tolerate concentration of 0.037% bile salts after 24 h of incubation. Three strains were able to significantly reduce Salmonella Typhimurium levels in the crop and in the ceca of broiler-type chickens. Among the 12 antibiotics tested for antibiotic resistance, all strains were resistant to bacitracin and susceptible to gentamycin, neomycin, ormethoprim, triple sulfa, and spectinomycin. Bacterial spore formers have been shown to prevent gastrointestinal diseases in animals and humans. The results obtained in this study show important characteristics to be evaluated when selecting Bacillus spp. candidates to be used as probiotics.